Hospital nurse following robot: Hardware development and sensor integration - Bukhari, Ilias; Ramachandran, Nagarajan, Prof. Dr.; Murugappan, M.; K., Helmy; A. S., Awang Omar; M. A., Abdul Rahman (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Man Machine Systems (ICoMMS 2012) organized by School of Mechatronic Engineering, co-organized by The Institute of Engineer, Malaysia (IEM) and Society of Engineering Education Malaysia, 27th - 28th February 2012 at Bayview Beach Resort, Penang, Malaysia.